CT evaluated sarcopenia signals: Shorter survival for small cell lung cancer patients - Pekařová, A; Pekař, M; Daniš, D; Nováková, Z (Physiological research, 2021)
Sarcopenia is an independent risk factor for morbidity and mortality in patients suffering from small cell lung cancer (SCLC), however, a universal indicator of sarcopenia usable in clinical practice is still missing. A novel indicator for describing the severity of cancer could be helpful in tailoring the anti-tumor therapy. The aim of this study was to evaluate the computed tomography (CT) scans of total muscle area and radiation attenuation in patients suffering from small cell lung cancer. We used staging CT scans performed at the time of diagnosis to measure total muscle area (TMA) and average psoas density (PD) at level of the 3rd lumbar vertebra. TMA and PD were statistically evaluated in association with overall survival and disease staging. We used Mann-Whitney test and Spearman´s correlation coefficient for statistical testing and p-value under 0.05 was considered statistically significant. Retrospectively we examined 47 patients suffering from SCLC (mean age 65.05+/-7.3 years, BMI 23.97+/-4.4 kg/m2, BSA 1.77+/-0.2 m2, 30-day mortality was 4.3 % with 10 months median survival). As sarcopenia was pointed TMA under 55 and 39 cm2/m2 for men and women respectively. The sarcopenic patients had significantly shorter median survival (7 vs. 11 months, p=0.05). We observed a significant relationship between survival and performance status (Spearman´s correlation, R=-0.39, p=0.05). The patients were divided into two groups according to the extensive (ED, n=34) or limited (LD, n=13) form of the disease. We observed significant difference in PD (42.49+/-6.1 vs. 47.67+/-4.5 HU, p=0.006) between ED vs. LD groups.
Keywords: Female; ženské pohlaví; Tomography, X-Ray Computed; nádory plic; Predictive Value of Tests; prediktivní hodnota testů; časové faktory; Time Factors; Health Status; lidé; zdravotní stav; malobuněčný karcinom plic; Psoas Muscles; prognóza; Humans; Risk Factors; retrospektivní studie; bederní svaly; Male; složení těla; Aged; Small Cell Lung Carcinoma; Sarcopenia; rizikové faktory; Prognosis; Body Composition; Lung Neoplasms; lidé středního věku; senioři; mužské pohlaví; sarkopenie; Retrospective Studies; Middle Aged; počítačová rentgenová tomografie